The richness of V2O5 polymorphs as superior cathode materials for sodium insertion. (20th April 2018) - Baddour-Hadjean, R.; Safrany Renard, M.; Emery, N.; Huynh, L.T.N.; Le, M.L.P.; Pereira-Ramos, J.P.
Abstract: In this paper, a special emphasis is given to the newly obtained electrochemical properties at room temperature of the two-dimensional ε′- and γ′-V2 O5 polymorphs as sodium intercalation compounds. The structural peculiarities and electrochemical properties of each phase are presented. A full electrochemical and structural reversibility is demonstrated for both compounds upon sodium insertion at high voltage of 2.8 V. This noticeable voltage enhancement (+1 V) compared to α-V2 O5 cathode is ascribed to the specific layers organization consisting of bilayered and puckered sheets in ε′-V2 O5 and γ′-V2 O5, respectively. Promising data, with large capacities (from 120 to 200 mAh g −1 ) and an excellent cycle life allow to identify new high performance V2 O5 - forms as positive electrode materials for sodium-ion batteries. Highlights: Novel layered vanadium oxides as cathode materials for NIBs. Facile room temperature synthesis of γ′-V2 O5 and ε′-V2 O5 . Voltage enhancement controlled by V2 O5 layers structuration. High stable capacities: 120–200 mAh g − 1 over 50 cycles.